Proposta de observação de aves como atividade estratégica à conservação ambiental no Jardim Botânico Benjamim Maranhão em João Pessoa - PB - Mélo, Bárbara Priscila Moreira de (2015)
Have long the birds are exerting enormous fascination on mankind and arousing sensations and ideas related to birth and death, love for music and freedom. Brazil is home to the third most diverse avifauna of the world, with over 1.900 species, making it one of the most important places to promote conservation action. The Atlantic Forest contributes prominently to the diversity of Brazilian avifauna featuring over 1020 resident species and endemism rate of 18%. The Botanical Garden of João Pessoa-PB has great potential for implementing birdwatching activities for this is necessary prior knowledge of the bird species found in areas trails used by local guides. Given the above, the main objective of this work is contribute to formulation proposal que use a birdwatching with a view to conservation in the Botanical Garden Benjamin Maranhão. The collections of information had held from April 2014 to January 2015, in the early hours of the day, a time when individuals go out to feed. The collections were made per transect following the tracks already used by the Botanical Garden guides. For the observation of birds was used 7x40 binoculars with magnification and identification was achieved using field notes and bird identification guides. Various bird species were also found along the trails and seven in the open area of the Botanical Garden. Among the species found are the following, which are typical rainforest: Tyrannus melancholicus, Ramphocelus bresilius, Chloroceryle americana, Aramus guarauna, Euphonia chlorotica, Stelgidopteryx ruficollis, Dendroplex picus, Crotophaga ani, Tangara cayana e Troglodytes musculus. Species observed in the garden can help to flag and umbrella species in the execution of conservation projects with a focus on ecotourism as much as in non-formal education programs in partnership with schools of public networks and private schools.